Trade-offs in cost and emission reductions between flexible and normal carbon capture and sequestration under carbon dioxide emission constraints. (November 2017) - Craig, Michael T.; Zhai, Haibo; Jaramillo, Paulina; Klima, Kelly
Highlights: Quantify CO2 emission and cost benefits of flexible CCS relative to normal CCS. Flexible CCS mostly reduces operational costs via reserve costs. Flexible reduces costs but increases CO2 emissions under a moderate emission limit. Flexible versus normal CCS pose near- and long-term tradeoffs to policymakers. Abstract: Relative to "normal" amine-based post-combustion capture carbon and sequestration (CCS), flexible CCS adds a flue gas bypass and/or solvent storage system. Here, we focus on flexible CCS equipped with a solvent storage system. A primary advantage of flexible over normal CCS is increased reserve provision. However, no studies have quantified system-level cost savings from those reserves, which could drive the public benefits and rationale for policy support of flexible over normal CCS. Here, we quantify total power system costs, including generation, reserve, and capital costs, as well as carbon dioxide (CO2 ) emissions of generator fleets with flexible versus normal CCS. We do so under a moderate and strong CO2 emission limit. Relative to normal CCS, solvent storage-equipped flexible CCS reduces system-wide operational plus annualized CCS capital costs but increases system-wide CO2 emissions under the moderate limit, whereas it reduces system-wide costs and emissions under the strong limit. Under both limits, we find that reductions in reserve costs constitute 40–80% of the reductions in total operational costs with flexible CCS rather than normal CCS. Thus, flexible versus normal CCS deployment decisions pose cost and emissions tradeoffs to policymakers under a moderate emission limit as well as tradeoffs between near- and long-term policy objectives.